SEPARATE ASPECTS OF THE DEMOGRAPHIC SITUATION IN UZBEKISTAN AND ITS ASSESSMENT IN GEOGRAPHICAL CONTEXT - Komilova, Nilufar Kh.; Mukhammedova, Nazokat J.; Abdalova, Zulkhumor T.; Nazarov, Mamatkodir I.; Kurbanov, Pahlavon R. (International Journal of Psychosocial Rehabilitation, 2020)
. The problems of demographic development in the modern world are becoming increasingly important. The rapid growth of the world population, lack of resources, and the intensification of migration processes make it difficult to ensure a decent standard and quality of life on the Planet. Therefore, the main purpose of the paper is to analyse certain aspects of the demographic situation in Uzbekistan and its assessment in a geographical context. Theoretical researches in studying mortality and life expectancy base their conclusions on identifying the main trends and causes of mortality in certain countries in certain periods. It is well known that the study of the mortality rate of the population is extremely complex and has attracted interest of a wide range of disciplines: medical workers, demographers, economic geographers, sociologists and other specialists. However, it should be noted that in the Republic special scientific researches on geographical aspects of this problem are conducted in a rather narrow way. The paper found that climate change significantly affects the life expectancy of the population. It was determined that the increase in mortality rates is also closely related to magnetic storms. At the same time, the authors noted that the infant mortality rate has declined slightly in recent years.